Manajemen Issue Dalam Proses Politik di Aceh - Saidaturrahmah, Saidaturrahmah; Samosir, Hasrat Efendi; Hasan, Kamaruddin (FISIP Universitas Malikussaleh, 2024)
Aceh, as a special autonomous province in Indonesia, has garnered national and international attention due to its long-standing history intertwined with conflict and peace. The political process in Aceh is closely tied to various complex issues that impact its stability, socio-economic development, and the relationship between the central government and Aceh. This scholarly article aims to analyze issue management in the political process in Aceh, with a focus on the post-MoU Helsinki 2005 period. In this article, the author discusses how political issues, such as special autonomy, identity, and issues related to the Aceh Governance Law (UUPA), influence Aceh's politics and its relationship with the central government. How issue management can be applied in the context of Aceh's politics to ensure political stability and sustainable development. This article employs a qualitative method with data collection techniques through literature review. The discussion has covered the definition of the issue, focusing on key political issues in Aceh, such as special autonomy, identity, and UUPA-related issues. The steps in issue management in Aceh's politics, including dialogue, community participation, institutional strengthening, effective communication, advocacy, and evaluation. Issue management is key to handling these political issues and achieving stability and sustainable development in Aceh.